2017
DOI: 10.1136/annrheumdis-2017-211414
|View full text |Cite
|
Sign up to set email alerts
|

Cross-phenotype association mapping of the MHC identifies genetic variants that differentiate psoriatic arthritis from psoriasis

Abstract: ObjectivesPsoriatic arthritis (PsA) is a chronic inflammatory arthritis, with a strong heritable component, affecting patients with psoriasis. Here we attempt to identify genetic variants within the major histocompatibility complex (MHC) that differentiate patients with PsA from patients with cutaneous psoriasis alone (PsC).Methods2808 patients with PsC, 1945 patients with PsA and 8920 population controls were genotyped. We imputed SNPs, amino acids and classical HLA alleles across the MHC and tested for assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 23 publications
2
48
0
Order By: Relevance
“…A second analysis, with age of psoriasis onset considered as a covariate, found that the primary risk for PsA in psoriasis patients derives from asparagine (as found in HLA-B*27) or serine (in B*07 and B*08) residues at amino acid position 97 of HLA-B (Fig. 4b) 117 . The discrepancy between the two studies may reflect differences in the clinical subtypes between PsA cohorts in the two studies, as there is evidence that HLA-B allelic associations may differ with PsA clinical phenotype 189 .…”
Section: [H1] Mechanisms Of Hla Disease Associationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A second analysis, with age of psoriasis onset considered as a covariate, found that the primary risk for PsA in psoriasis patients derives from asparagine (as found in HLA-B*27) or serine (in B*07 and B*08) residues at amino acid position 97 of HLA-B (Fig. 4b) 117 . The discrepancy between the two studies may reflect differences in the clinical subtypes between PsA cohorts in the two studies, as there is evidence that HLA-B allelic associations may differ with PsA clinical phenotype 189 .…”
Section: [H1] Mechanisms Of Hla Disease Associationsmentioning
confidence: 99%
“…Interestingly, joint-infiltrating CD8 + T cells that, unusually, produce IL-17 have been detected in patients with PsA 115 . Indeed, arthritis risk in psoriasis patients has been linked to HLA-B*27, specifically glutamic acid at position 45 116 and asparagine at position 97 117 , both of which are located in the peptide-binding groove and likely to influence peptide presentation (Fig. 4b) 118 .…”
Section: [H1] Mechanisms Of Hla Disease Associationsmentioning
confidence: 99%
“…To date, the HLA-B27 region represents the strongest genetic risk association identified in axSpA, PsA and reactive arthritis [31][32][33] , and positivity for HLA-B27 is strongly associated with sacroiliitis in both AS and PsA. In addition, multiple other variants within the MHC class I loci are associated with PsA (including HLA-B39, HLA-Cw6, HLA-B38 and HLA-B08) or AS (HLA-A02, HLA-B07), with some associations most evident when patients are stratified by clinical characteristics 30,[34][35][36] . The association of SpA with a variety of different HLA-B loci indicates that several immunological mechanisms could be altered by these genetic associations, including T cell repertoire selection and antigen presentation 37 .…”
Section: Genetics Of Spa With a Focus On The Mhc Class I Pathway And mentioning
confidence: 99%
“…However, after adjusting for HLA‐B amino acid position 45, the differential effect of HLA‐C*06:02 lost significance. Bowes et al found HLA‐C*06:02 to be less common in patients with PsA compared with psoriasis and that HLA‐C*06:02 had significant association with younger age of psoriasis onset . However, once the data were controlled for the age of onset, there was no association of HLA‐C*06:02 with PsA.…”
Section: Hla‐c Associations With Psamentioning
confidence: 99%